A Study on the Surface Image Processing of the Mixed Mineralized Lining - Eun Kim, Tae; ., . (International Journal of Engineering and Technology, 2018)
relationships, which are relatively important when intending to obtain the information of the objects from the contrast images, and for finally detecting the areas of the problems that look like the faults from the images (linings) of the solid bodies that are materialized with the mixed minerals is proposed. Methods/Statistical analysis: By extracting the interested areas on real time by using the background differential images and by dividing the interested areas by carrying out a principal component analysis and by calculating the vector relations, whether or not there is a lining fault is decided. Findings: This research proposes an image handling method that detects and classifies the problematic areas that look like the faults from the lining images which are materialized with the mixed minerals that were entered through the camera, and it shows the examples in which the method was actually applied. Improvements/Applications: The method being proposed will be applied for automatically detecting the cracked parts on the surface of the lining, for classifying the types, and measuring the extent of the fault.